MACRO AND MICRO-MINERAL STATUS OF FEEDS AND FODDERS IN VILLAGES OF DATIWADA TALUKA OF NORTH GUJARAT REGION (Indian Journal of Animal Production and Management, 2013)
A survey was carried out in ten villages of Dantiwada taluka of the Banaskantha district which are adopted by Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, to know the macro and micro-minerals status in feeds and fodders by samples at random. The samples were analysed for macro minerals, calcium and phosphorus with micro minerals cupper, manganese and zinc. The concentrate samples were analysed individually and in combination with other ingredients, as per as their practically utility to dairy animals. The results of analysis were compared with the critical level for particular micro minerals level and percentages of samples which contained micro minerals below critical level were calculated.
Keywords: Macro and Micro minerals; survey; Feeds; Fodders